2013
DOI: 10.1002/emmm.201302663
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis revealed the molecular mechanism underlying RBM10‐mediated splicing regulation

Abstract: RBM10 encodes an RNA binding protein. Mutations in RBM10 are known to cause multiple congenital anomaly syndrome in male humans, the TARP syndrome. However, the molecular function of RBM10 is unknown. Here we used PAR-CLIP to identify thousands of binding sites of RBM10 and observed significant RBM10–RNA interactions in the vicinity of splice sites. Computational analyses of binding sites as well as loss-of-function and gain-of-function experiments provided evidence for the function of RBM10 in regulating exon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
209
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(224 citation statements)
references
References 51 publications
14
209
1
Order By: Relevance
“…Differential splicing analyses comparing RBM10 LoF mutant tumors (n = 32) and samples WT for all splicing factor genes (n = 87) identified exon inclusion as the primary alternative splicing event in both LUAD and BLCA (Figure 4C; Figure S3A; Tables S2 and S3). This is consistent with earlier reports correlating the overexpression of RBM10 in HEK293 cells with exon skipping (Wang et al, 2013). …”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Differential splicing analyses comparing RBM10 LoF mutant tumors (n = 32) and samples WT for all splicing factor genes (n = 87) identified exon inclusion as the primary alternative splicing event in both LUAD and BLCA (Figure 4C; Figure S3A; Tables S2 and S3). This is consistent with earlier reports correlating the overexpression of RBM10 in HEK293 cells with exon skipping (Wang et al, 2013). …”
Section: Resultssupporting
confidence: 94%
“…Interestingly, RBM10 expression has also been shown to correlate with retention of the introns flanking the exons that are skipped due to its activity (Wang et al, 2013; Figure S3C), and we observed the corresponding normal splicing of these introns upon RBM10 loss in LUAD (Figure 4D). The majority of genes with this pattern of altered splicing by RBM10 LoF mutation were upregulated compared to RBM10 WT samples, suggesting that RBM10-mediated cassette exon repression acts as an overall gene regulatory mechanism.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…The read alignment BAM files produced by TopHat and the Hg19 alternative events annotations downloaded from the MISO main page served as an input. The software computed the percentage of transcripts that were spliced to include exons, known as the PSI (Ψ) [26]:…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…25,26 NUMB isoform switch is regulated by RBM10, which, importantly, is one of the most frequently mutated genes in lung cancer. 27,28,29,30 This work opens a possible therapeutical avenue to regulate NUMB splicing with chemically modified antisense oligonucleotides, thereby reversing the effect on proliferation, which is the topic of ongoing investigation.…”
Section: Epigenetic Regulation and Genome Organizationmentioning
confidence: 99%